A rare cause of pregnancy-related acute kidney injury-infective endocarditis-associated infection-related glomerulonephritis (Indian Journal of Case Reports, 2024)
Pregnancy-related acute kidney injury (PRAKI) commonly occurs due to septic abortion and accounts for 15–25% of acute kidney injury (AKI). Glomerulonephritis is a rare cause of PRAKI. The index case was a 20-year-old primigravida who presented in the last trimester of pregnancy with infective endocarditis-associated glomerulonephritis, also complicated by splenic infarct, AKI, and intrauterine fetal death. Renal biopsy revealed crescentic glomerulonephritis and she improved on antibiotic and steroid therapy.